Effectiveness of a Virtual Reality Head-Mounted Display System-based Developmental Eye Movement Test - Jung-Ho Kim; Ho-Jun Son; Sung-Jin Lee; Deok-Young Yun; Soon-Chul Kwon; Seung-Hyun Lee (Journal of Eye Movement Research)
By transplanting the Developmental Eye Movement (DEM) test chart to a virtual reality head-mounted display (VR HMD) system, this study sought to evaluate the effectiveness of the DEM test for measuring dynamic visual acuity. Thirty-nine adults aged 20–39 years of both genders were the subjects of the study. After undergoing measurement of their visual function, through medical questionnaire, interpupillary distance, near point of convergence (NPC), near point of accommodation (NPA), and far and near phoria, the correlation between the tests was analyzed performing DEM vertical, horizontal test and VR HMD DEM (VHD) vertical, horizontal test. NPC and NPA decreased significantly after the VHD test, while phoria did not. The horizontal was quicker than the vertical in the DEM test, and vice versa in the VHD test. DEM was quicker than VHD in both the vertical and horizontal directions. There was no notable difference in error frequency between DEM and VHD. In terms of DEM and VHD test, there was no notable difference in the short-range IPD and subjective symptoms of the top 10 and bottom 10 subjects. There was also no notable difference between the exercise and non-exercise groups and the game and non-game groups. The performance time for VHD, in which the chart must be read while moving the body, was longer than that of DEM. Therefore, based on the consistency of the results of both tests and the lack of a difference in error frequency and subjective symptoms, the VHD equipment proposed in this thesis is as effective as dynamic visual acuity measurement equipment. In addition, the lack of a difference between the exercise and non-exercise groups and the game and non-game groups demonstrated that the amount of exercise and game by an ordinary person does not influence their dynamic visual function.